2020
DOI: 10.3390/insects11060335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drimys winteri (Canelo) Essential Oil as Insecticide against Acanthoscelides obtectus (Coleoptera: Bruchidae) and Aegorhinus superciliosus (Coleoptera: Curculionidae)

Abstract: Adverse effects caused by synthetic pesticides have increased interest in plant-derived insecticidal compounds, in particular essential oils, as a more compatible and ecofriendly alternative for pest control of economic importance. For this reason, the essential oil isolated from leaves and shoots of Drimys winteri (J.R. Forster & G. Forster)—also named canelo (CEO)—was investigated for its chemical profile and insecticidal action against Acanthoscelides obtectus (Say)—one of the most important post-harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…The study and use of essential oils is an interesting and potentially useful tool by which to develop auxiliary insecticides 31 . PEOs have good prospects in the control of scale insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study and use of essential oils is an interesting and potentially useful tool by which to develop auxiliary insecticides 31 . PEOs have good prospects in the control of scale insects.…”
Section: Discussionmentioning
confidence: 99%
“…The study and use of essential oils is an interesting and potentially useful tool by which to develop auxiliary insecticides. 31 PEOs have good prospects in the control of scale insects. Ro is an aromatic plant oil rich in bioactive compounds with high value in the food, pharmaceutical and cosmetic industries, 32 but research on its insecticidal activity has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The GC oven temperature started at 40 • C for 3 min, then increased to 250 • C at a rate of 5 • C/min. This analytical method has been previously validated [28]. Afterward, monoterpenes were identified using a series of alkanes (C 9 -C 18 ) by comparing the experimental and theoretical Kovats indices (KI) of each compound according to the National Institute of Standards and Technology (NIST) library.…”
Section: Characterization Of the Essential Oilsmentioning
confidence: 99%
“…Both sexes of the raspberry weevil stayed for very short times in the treated area with the oil (<0.8 min), showing a homogeneous repellency in the species. The data suggest that canelo leaves and shoots essentials oils have an insecticide effect (Tampe et al, 2020).…”
Section: Plaguicidal Activity: Insecticidal Activitymentioning
confidence: 99%